Ana’u Sengkatau Praktik Toleransi Beragama di Perbatasan Indonesia-Filipina - Sunandar Macpal; Irwan Abdullah (UIN Raden Mas Said Surakarta, 2019)
This research aims to elaborate on the concept of ana’u senkatau, which is understood and implied by Kawaluso society to prevent tolerance among religious society. The research employs ethnography method as apart of the qualitative approach. To collect the data, this research observes the phenomenon within in-depth interview. The result shows ana’u senkatau concept, in fact, it has existed in Sangihe before the religions come in. The existence of religion allows ana’u senkatau concept, and the religious institutions, altogether with the society, maintains the concept. The ana’u senkatau concept has been similar to a family clan that becomes center for social services such as marriage control, distribution inherits land, and workmanship farm. In other words, ana’u senkatau concept becomes a solution for reducing intolerance among religions.